PERAN PEMUDA SEBAGAI KADER BELA NEGARA DALAM MENDUKUNG PERTAHANAN DAN KEAMANAN MARITIM - Merry Kathryn Kurniawati Br Panjaitan (Jurusan Ilmu Hubungan Internasional, 2017)
This paper explains to what extent the role of youth as a the state cadre of national defensecan contributein supporting maritime security, especially on the outer islands of the Republic of Indonesia. This article seeks to raisenew ideasabout youth planning activities in order to foster maritime culture for buildingIndonesia as a world maritime fulcrum.As part of the whole society, the role of youth is of importance forchannellingtheir talents, creativity, spirit and real active role in state development which is based on community service.